RESULTS OF OPTIMIZATION OF PARAMETERS AND OPERATING MODES OF THE DISK PNEUMATIC SOWING DEVICE - V. V. Golubev; A. S. Firsov; D. M. Rula (Сельскохозяйственные машины и технологии, 2015)
Technological effectiveness and qualitative characteristics of pneumatic sowing devices are higher than ones of lots produced rollers for a number of reasons, caused by decrease in number of doubles, increased evenness of seeds in a row. The major studied factors were selected and levels of their variation were established. A laboratory installation for optimization of the main technical and constructive characteristics on applied sowing devices was created. A disk pneumatic sowing device (DPSD) design with application block and modular principle of design for crops the smallseeded crops was working out. Optimum value of studied parameters and DPSD operating modes were established. Optimum value of evenness of seeds along the row, making 1.14-1.16 mm with a frequency of rotation of a sowing disk 75- 80 rpm, diameter of seed cells in a sowing disk 2.31-2.32 mm and pressure of an air stream 2.5-2.6 kPa were defined. The better distribution of seeds along a row in comparison with the production roller seeding mechanism when smallseeded crops sowing. It was recommended the offered design with the optimized parameters and operating modes for flax sowing and firm granulated mineral fertilizers application depending on cultivation conditions and functioning of sowing section.